Sati Kasturba : a life-sketch, with tributes in memoriam - Prabhu, R. K. (Ramachandra Krishna), 1883-1966 (SAMP early 20th-century Indian books project, 1944)
On the life of Kasturba Gandhi, 1869-1944, wife of Mahatma Gandhi, 1869-1948, Indian statesman.